Intergenerational relations: the use of technology as a mediator - Raymundo, Taiuani Marquine; BERNARDES, M. S; SANTANA, C. S. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
The social dynamics of today provide greater proximity between people belonging to different generations, diluting the differences among the large volume of innovations, whether technological or cultural that are produced continuouslyÂ¹. Intergenerational relationships can bring great benefits to the young and older, who may learn together through their experience, the mutual exchange of knowledge or merely for the daily contactÂ². Goal: Understanding how young monitors participants of a digital inclusion project for seniors (PIDI) relate to the elderly, which are the benefits of this relationship and the changes it brings in the life and family environment of these young people. Method: This is a qualitative, cross-sectional and descriptive study. Data collection was conducted through a questionnaire with open questions. The responses were analyzed and grouped according to their content. Results: 16 monitors who participated in the PIDI took part in this study (students with scholarship and volunteers), of which 69% are women and 31% are men, with an average age of 25. Regarding the time of participation in the project, 44% attended for six months, 25% for a year and 31% more than one year. 62.5% of them considered the relationship with the elderly as excellent and 37.5% considered as good. The monitors report that the process of teaching the elderly is facilitated due to the fact that the elderly are willing to learn and that the relationship established in this process is very natural. According to the monitors, the elderly are understandable and have patience forward to exchanging roles in which the young are teaching the older. The monitors also report that they learned to be more patient, be aware of difficulties, be more caring, respect differences, to listen more, to recognize specific characteristics of the elderly, in addition to personal growth. Young people report that they were able to transfer what they have learned in the relationship with the elderly for their family environment reporting that they began to act with more patience and tolerance, now have a closer interaction with elderly relatives, and better understand their difficulties and recognize their potential and, they start to assist and teach family members in the use of electronic devices. Conclusion: The intergenerational interaction is a valuable tool to exclude preconceptions, for the transfer of knowledge, mutual aid, solidarity and friendship.